Exploring the diversity of Shan Tea in Vietnam through SSR markers, morphological traits, and biochemical content - Bui, Khuynh The; Dinh, Thai Hoang; Vu, Ngoc-Thang; Dang, Van Thu; Do, Thi Viet Ha; Li, Xinghui; Trans, Xuan Hoang (Penerbit Universiti Kebangsaan Malaysia, 2025)
Shan tea (Camellia sinensis var. Shan), a variety native to the mountainous regions, used to prepare ‘Che Shan Tuyet’- a high quality standard tea product with cultural significance, is considered the most precious tea in Vietnam. However, little is known about its genetic diversity, composition, and variation in biochemical content across the central growing regions until now. Here, the use of 30 pairs of SSR primers selected based on their proven high utility in previous studies in tea with high polymorphisms showed that the Shan tea population exhibit rich genetic diversity, with gene diversity (H) varying from 0.47 to 0.82 and the polymorphic information content (PIC) ranging from 0.47 to 0.84. The cluster (UPGMA-based) analysis showed that 60 Shan tea accessions can be categorized into three groups with different origins. Biochemical profiles including tannin and catechins were observed to have high variation by harvest season of which the highest content was recorded during summer. Though the variation in biochemical profiles was not considerably significant among the three groups of origin, accessions from Suoi Giang (Yen Bai) significantly had lower content of tannin, EC, ECG, and EGC compared to Shan tea in Cao Bo (Ha Giang). In addition, morphology-based PCA also showed that it is practical to discriminate three groups of different origins, with the essential traits being leaf blade width, pericarp thickness, leaf area (PC1), fruit length, and fine pluck weight (PC2). The clustering of 60 Shan accessions based on morphological traits also showed consistent results with the genetic diversity analysis conducted using SSR, where accessions from Suoi Giang and Cao Bo had higher similarity levels than accessions from Tua Chua.